The relationship between self-cohesion and smartphone addiction: the mediating role of rejection sensitivity - Mogeda El Sayed El Keshky; Huda Aseem; Amira Alzain; Yasser Abdelazim Abdelmawgoud Samak (Frontiers Media S.A., 2023)
BackgroundThe increasing use of smartphones with attractive applications has yielded concerns over problematic overuse, also called smartphone addiction, thus creating a need to investigate the antecedents and pathways of this addiction.ObjectiveThe aim of this study was to investigate the relationships between the self-cohesion dimensions of presence and consistency and smartphone addiction, and the potentially mediating role of rejection sensitivity.MethodsA total sample of 910 respondents (58% females, mean age = 34.9, SD = 13.6) participated in the study. They completed a questionnaire including demographic characteristics and queries about frequency and duration of smartphone use, as well as the Self-Cohesion Scale, the Short Version of Smartphone Addiction Scale, and the Rejection Sensitivity RS-Adult Questionnaire. Structural equation modeling was used to examine the relationships in question.ResultsThe findings indicated that smartphone addiction was positively correlated with rejection sensitivity and negatively correlated with the self-cohesion dimensions of presence and consistency. Further, both presence and consistency were negatively associated with smartphone addiction and rejection sensitivity negatively mediated these relationships.ConclusionSelf-cohesion and rejection sensitivity appear to be important predictors of smartphone addiction. Efforts to counteract smartphone addiction should, therefore, endeavor to increase smartphone users' self-cohesion and reduce their rejection sensitivity.